A convergence theorem for a finite family of multivalued k-strictly pseudononspreading mappings in ℝ-trees - Khanitin Samanmit (2018)
© 2015 by the Mathematical Association of Thailand. All rights reserved. In this paper, we introduce a new m-step iterative process for finite family of k−strictly pseudononspreading multivalued mappings in ℝ-trees. We obtain a strong convergence theorem of m-step iterative method to a common fixed point of a finite family of those multivalued mappings in ℝ-trees. Our results extend many known recent results in the literature. We close this work with the first examples of k-strictly pseudononspreading multivalued mappings in ℝ-trees.